2008
DOI: 10.1128/jb.01677-07
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Group BStreptococcusCsrRS Regulon and Effects on Pathogenicity

Abstract: CsrRS (or CovRS) is a two-component regulatory system that controls expression of multiple virulence factors in the important human pathogen group B Streptococcus (GBS). We now report global gene expression studies in GBS strains 2603V/R and 515 and their isogenic csrR and csrS mutants. Together with data reported previously for strain NEM316, the results reveal a conserved 39-gene CsrRS regulon. In vitro phosphorylationdependent binding of recombinant CsrR to promoter regions of both positively and negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
116
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(124 citation statements)
references
References 31 publications
7
116
0
Order By: Relevance
“…An orthologue of the CsrRS system has been identified in GBS (27,31). Expression profiling studies suggest that as many as 7% of GBS genes are regulated by CsrRS (28,31). The CsrRS regulon includes genes that encode secreted or surface components and transport systems for various small molecules, including peptides, amino acids, sugars, and metals.…”
mentioning
confidence: 99%
“…An orthologue of the CsrRS system has been identified in GBS (27,31). Expression profiling studies suggest that as many as 7% of GBS genes are regulated by CsrRS (28,31). The CsrRS regulon includes genes that encode secreted or surface components and transport systems for various small molecules, including peptides, amino acids, sugars, and metals.…”
mentioning
confidence: 99%
“…While CovR generally appears to act as a repressor in GAS, GBS, and S. mutans, there are a few reports in which CovR functions as an activator (36,42). The GAS dppA promoter (PdppA) is one such example, the expression of which is stimulated about 4-fold by CovR (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the case of GBS, CovR has been shown to stimulate the expression of two genes: cfb, which encodes the CAMP factor; and SAG-2042, which encodes a rhodanase-like protein (42). In vitro binding of CovR was demonstrated for the promoter of the cfb gene (Pcfb) (42), but, unlike GAS PdppA, the exact location of CovR binding to Pcfb has not been mapped, and it is not known whether CovR requires any additional factors for stimulation of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that transcription of the cylE gene in the ⌬stp1 mutant was not significantly different when compared with the isogenic WT (-fold difference compared with WT ϭ 0.92 Ϯ 0.1; Table 3). In GBS, the two-component regulator CovR binds to the promoter of hemolysin (P cylX ) and represses transcription of the cyl operon, including cylE (37,47,49,78). Because Stk1 regulates cylE transcription through phosphorylation of CovR (37), it was of interest to examine whether Stp1 regulation of ␤-H/C required the hemolysin repressor, CovR.…”
Section: Gbs Deficient In Stp1 Expression Exhibit Attenuatedmentioning
confidence: 99%